Tropospheric SF6: Age of air from the Northern Hemisphere midlatitude surface. Issue 19 (10th October 2013) - Waugh, D. W.; Crotwell, A. M.; Dlugokencky, E. J.; Dutton, G. S.; Elkins, J. W.; Hall, B. D.; Hintsa, E. J.; Hurst, D. F.; Montzka, S. A.; Mondeel, D. J.; Moore, F. L.; Nance, J. D.; et al.
Abstract [1] Observations of SF6 are used to quantify the mean time since air was in ("mean age" from) the Northern Hemisphere (NH) midlatitude surface layer. The mean age is a fundamental property of tropospheric transport that can be used in theoretical studies and used to evaluate transport in comprehensive models. Comparisons of simulated SF6 and an idealized clock tracer confirm that the time lag between the SF6 mixing ratio at a given location and the NH midlatitude surface provides an accurate estimate of the mean age. The ages calculated from surface SF6 measurements show large meridional gradients in the tropics but weak gradients in the extratropics, with near‐zero ages at the surface north of 30°N and ages around 1.4 years south of 30°S. Aircraft measurements show weak vertical age gradients in the lower and middle troposphere, with only slight increases of age with height in the NH and slight decreases with height in the Southern Hemisphere. There are large seasonal variations in the age at tropical stations (annual amplitudes around 0.5–1.0 year), with younger ages during northern winter, but only weak seasonal variations at higher latitudes. The seasonality and interannual variations in the tropics and Southern Hemisphere are related to changes in locations of tropical convection. There is qualitative agreement, in both spatial and temporal variations, between the simulated ages and observations. The model ages tend to be older than observed, with differences of ~0.2 year in the Northern Hemisphere upper troposphere and throughout the Southern Hemisphere troposphere.